Modeling, construction and experimental validation of actuated rolling dynamics of the cylindrical Transforming Roving-Rolling Explorer (TRREx). (March 2017) - Edwin, L.; Mazzoleni, A.; Gemmer, T.; Ferguson, S.
Abstract: Planetary surface exploration technology over the past few years has seen significant advancements on multiple fronts. Robotic exploration platforms are becoming more sophisticated and capable of embarking on more challenging missions. More unconventional designs, particularly transforming architectures that have multiple modes of locomotion, are being studied. This work explores the capabilities of one such novel transforming rover called the Transforming Roving-Rolling Explorer (TRREx) . Biologically inspired by the armadillo and the golden-wheel spider, the TRREx has two modes of locomotion: it can traverse on six wheels like a conventional rover on benign terrain, but can transform into a sphere when necessary to negotiate steep rugged slopes. The ability to self-propel in the spherical configuration, even in the absence of a negative gradient, increases the TRREx's versatility and its concept value. This paper describes construction and testing of a prototype cylindrical TRREx that demonstrates that "actuated rolling" can be achieved, and also presents a dynamic model of this prototype version of the TRREx that can be used to investigate the feasibility and value of such self-propelled locomotion. Finally, we present results that validate our dynamic model by comparing results from computer simulations made using the dynamic model to experimental results acquired from test runs using the prototype.